Ayurvedic Perspectives on the Management of Skin Diseases – A Review - Kumar Sourtha, Mahendra (International Research Journal of Ayurveda & Yoga, 2025)
Numerous factors can contribute to skin issues, including allergies, autoimmune diseases, and genetics. Kushtha, a sickness marked by skin derangement, is the umbrella term used by Ayurveda to describe skin problems. When considering the incidence of various diseases, skin disorders account for more than 20% of all medical visits worldwide each year. Depending on the severity of the symptoms and the prognosis, all Acharyas classify Kushtha as either Maha Kushtha or Kshudra Kushtha. The Ayurvedic medical system describes a wide range of etiological variables and illness management techniques. When Tridosha, Twak, Rakta, Mamsa, and Lasika are vitiated, Kushtha results. Therefore, Dosha and Dushya’s involvement is the foundation of Kushtha’s management. The basic idea of treatment is the same for all types of Kushtha, even though some treatment approaches are condition specific. Acharya has highlighted the need for Raktamokshana to eject Dushita Rakta, the primary Dushya in the pathology of Kushtha, and Shodhana (detoxification) therapy to remove the morbid Dosha from the body. Both internal and external drugs, such as Rasa Aushadhi, Churna, Kwath, Asav, Arishta, Guggulu, Ghrita, and Malhara, Tail, Lepa, are part of the Shamana (palliative) therapy. In Ayurveda, dietary control, Dincharya, Ritucharya, Rasayana treatment, and Sadvritta are all highly valued for maintaining good health and preventing illness. To create Ayurvedic-based guidelines for the treatment of skin conditions, it is necessary to examine this holistic perspective of detoxification, palliative care, and lifestyle change.